Financial strain mediates the relationship between socioeconomic status and smoking - Waters, Aaron F. (Tob Prev Cessat, 2019)
INTRODUCTION: Smoking is the leading cause of preventable death accounting for about 0.48 million deaths in the US every year. Across the socioeconomic status (SES) gradient smoking prevalence differs greatly, with those of lower SES smoking at much higher rates than those of higher SES. Previous studies have shown relationships between socioeconomic status, financial strain, and smoking. However, little research has explored the possibility that financial strain might mediate the relationship between socioeconomic status and smoking. Thus, the goal of the current study was to determine whether financial strain was a mediating factor in the relationship between socioeconomic status and smoking. METHODS: Participants (N=238) were primarily female (67.6%) and African-American adults (51.7%) from the Dallas metropolitan area. The majority of the sample reported that they did not currently smoke (n=164). Participants who reported currently smoking at baseline (n=74) smoked an average of 9.96 (SD=10.79) cigarettes per day. RESULTS: Analyses revealed that financial strain partially mediates the relationship between socioeconomic status and smoking status. Additionally, financial strain was found to significantly partially mediate the relationship between socioeconomic status and cigarettes smoked prospectively over the next 7 days. CONCLUSIONS: Overall, findings suggest that greater financial strain may be one factor that links SES with current smoking and smoking level among those who smoke.